Enhanced recovery and restriction mapping of DNA fragments cloned in a new lambda vector. - Whittaker, P A (1988)
In this paper we describe a modification to the lambda vector EMBL3 which greatly expedites the construction of restriction maps of cloned DNA sequences. In the modified vector, EMBL3cos, all the phage coding sequences are placed to the right of the cloning sites so that the left cohesive end is separated by only 200bp, rather than 20kb (as in conventional lambda vectors), from the inserted DNA fragment. We show that reliable restriction maps can be rapidly constructed from partial digests of clones made in this vector by labelling the left cohesive end with a complementary 32P-labelled oligonucleotide. In addition, we quantify the restriction of clones containing human DNA by the McrA and McrB systems of E. coli and show that the use of Mcr- plating strains can increase the yield of recombinant phage up to tenfold, to give cloning efficiencies of greater than or equal to 10(7) pfu/microgram of human DNA.